LUMBOSACRAL TRANSITIONAL VERTEBRAE IN PATIENTS VISITING TERTIARY CARE HOSPITAL OF KHYBER PAKHTUKHWA: A RADIOLOGICAL STUDY - Aamir, Shabnum; Imtiaz, Humaira; Rehman, Zainab; Ambreen, Sadaf; Ghani, Fazal; Naoureen, Ayesha (Journal of Ayub Medical College Abbottabad, 2020)
Background: Lumbosacral transitional vertebra is a common anatomical variant of the spine that possibly is related to low back pain. The objective is to determine the frequency of Lumbosacral Transitional Vertebrae on lumbosacral radiographs in patients with low back pain visiting Neurosurgery OPD of Khyber Teaching Hospital Peshawar Khyber Pakhtunkhwa (KP). Method: This cross-sectional study was conducted on radiographs of lumbosacral spine in patients visiting for low back pain to the Neurosurgery OPD of Khyber Teaching Hospital Peshawar. A total of 300 anteroposterior (AP) and lateral lumbosacral plain radiographs were studied for the variation in lumbosacral spinal segment. The transition was classified according to the scheme used by Castellvi. Results: Among a total of 300 patients, normal anatomy of lumbosacral segments was observed in 215 patients (72%). About 85 cases (28%) showed Lumbosacral Transitional Vertebrae. The relationship of vertebral variation with age and gender was not observed. With regard to morphology, 29 (34.1%) patients had Castellvi type I, 26 cases (30.5%) were observed with Castellvi type II and 12 patients (14.1%) had type III while 18 cases (21.2%) had type IV transitional morphology. Conclusion: Lumbosacral Transitional Vertebrae are commonly found in patient with low back pain. Identification of Lumbosacral Transitional Vertebrae is clinically important to prevent an intervention at an incorrect vertebral level. Keywords: Lumbosacral Transitional Vertebrae; Low back pain; Lumbosacral radiographs